Dukungan lingkungan sosial terhadap aktivitas peran-ganda perempuan kelas menengah etnik Sunda (studi kasus di Kabupaten Garut) - Iriany, Ieke Sartika (Jurnal Abmas, 2003)
This research forms the case study of the middle-class Sundanese women's multiplied roles in Garut Regency. This research analyzes aspects of married women's perception of work activities in the domestic and public sectors, their husbands' perception of women's multiplied roles, and the Sundanese social environment's support for women's multiplied roles. The research question is: "Why Sundanese women's multiplied roles, as women's self-actualization in family and society, cannot contribute to development?". The method used in this research is the case study with a qualitative-descriptive approach. Data gathering techniques used observation-participation and in-depth interviews involving twenty-three general informants and eighteen key informants selected via the snowball technique. The result of the research shows that the Sundanese ethnic women (the wife) and the husbands of the middle class have a positive perception toward women's multiplied roles, so that the activities in implementing domestic roles and public roles are purposed to build a prosperous family, "Sakinah, mawaddah, warokhmah" ("peaceful, quiet, and merciful"), and have support from the social environment. Women's multiplied roles of Sundanese get significant support either from the family environment, the occupational environment, or their social environment. The women's multiplied roles model are the "ideal-roles model" or "equilibrium model," which means role differentiation in the family has integrated with the proportion of women's roles in the domestic sector (PSD) being equal to women's roles in the public sector (PSP). In another word, PSD is the same as PSP; with the "Trimatra Fungsional" paradigm (functional of three-dimensions paradigm) to perceive interaction dimensions of wife, husband, and children; so that role-structure differentiation according to functional goals can integrate.